2022
DOI: 10.1007/s40292-022-00520-x
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence About Aortic Valve Stenosis and Cardiovascular Hemodynamics

Abstract: Aortic stenosis (AS) is the most common degenerative valvular disease in western word. In patients with severe AS, small changes in aortic valve area can lead to large changes in hemodynamics. The correct understanding of cardiac hemodynamics and its interaction with vascular function is of paramount importance for correct identification of severe AS and to plan effective strategies for its treatment. In the current review with highlight the importance of pressure recovery phenomenon and valvular arterial impe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…ACEIs/ARBs also reduce blood pressure (BP) levels, hence decreasing the overall LV hemodynamic burden (5). Until a few years ago, ACEIs/ARBs were considered potentially harmful and even contraindicated in severe AS because they could potentially cause a rapid and harmful decrease in BP levels (6). However, a recent metaanalysis that included observational and randomized evidence indicated that ACEIs/ARBs could be harmless and could even be helpful for treating AS (4,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…ACEIs/ARBs also reduce blood pressure (BP) levels, hence decreasing the overall LV hemodynamic burden (5). Until a few years ago, ACEIs/ARBs were considered potentially harmful and even contraindicated in severe AS because they could potentially cause a rapid and harmful decrease in BP levels (6). However, a recent metaanalysis that included observational and randomized evidence indicated that ACEIs/ARBs could be harmless and could even be helpful for treating AS (4,7,8).…”
Section: Introductionmentioning
confidence: 99%